Microgravimetric method for the determination of metformin in pharmaceutical preparations and in the bulk drug - Tubino, Matthieu; Bianchessi, Luís Francisco; Vila, Marta Maria Duarte Carvalho (Eclética Química, 2016)
This article reports a microgravimetric method for the quantitative determination of metformin in bulk and in pharmaceutical preparations. The analysis is simple and relatively rapid. A complete analysis can be performed in only an hour and thirty minutes due to the drying procedure of the precipitate. However a sample can be treated every each five minutes. The method is based on the reaction of nickel (II) with metformin that in basic medium forms an orange precipitate. The reaction is performed in a plastic syringe. The filtration was done in a glass tube containing a sintered glass disk or in Millipore® syringe filters, with posterior weighing after drying. The analytical results were statistically compared with that obtained with a HPLC and with the titrimetric method suggested by the United States and by the Japanese pharmacopoeias.